Calcium fluoride doped silicon carbide preparation method, calcium fluoride doped silicon carbide, heat dissipation component and electronic equipment

Preparation of calcium fluoride-doped silicon carbide by hydrothermal reaction method solves the problems of complex, high cost and poor thermal conductivity of traditional silicon carbide preparation methods, achieves a more efficient and economical preparation process, and improves the material Thermal conductivity and density.

CN118851772BActive Publication Date: 2025-02-07INSPUR SUZHOU INTELLIGENT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411339079.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-07
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The preparation process of traditional silicon carbide preparation methods is complicated and the preparation cost is high, and the thermal conductivity of the prepared silicon carbide is poor.

Method used

Calcium fluoride-doped silicon carbide is prepared by hydrothermal reaction method. The composite powder is obtained by mixing calcium salt powder, acid solution and silicon carbide powder in anhydrous ethanol, and post-treatment of hydrothermal reaction, and then pressing and molding. Sintering gives dense calcium fluoride doped silicon carbide.

Benefits of technology

It realizes the preparation of silicon carbide materials with better thermal conductivity at a lower cost and higher efficiency, reduces the sintering temperature, and improves the relative density, hardness and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851772B_ABST
    Figure CN118851772B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing calcium fluoride-doped silicon carbide, calcium fluoride-doped silicon carbide, heat dissipation components and electronic equipment, and relates to the technical field of material preparation, the method comprising: using anhydrous ethanol as a solvent and tetramethylammonium hydroxide as a dispersant, mixing calcium salt powder, acidic solution and silicon carbide powder to obtain a suspension; subjecting the obtained suspension to a hydrothermal reaction, after the hydrothermal reaction is completed, treating the mixture obtained by the hydrothermal reaction to obtain a composite powder; pressing the obtained composite powder to obtain a green body, and sintering to obtain calcium fluoride-doped silicon carbide. The present invention prepares uniformly doped calcium fluoride-silicon carbide composite powder by a hydrothermal reaction method, and then granulates the powder and performs dry pressing to manufacture a green body, and then sintering the green body into a dense ceramic body, because the melting point of calcium fluoride is much lower than the melting point of silicon carbide, silicon carbide can be densified at a relatively low sintering temperature, while improving the relative density, the hardness and thermal conductivity of silicon carbide ceramics are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a method for preparing calcium fluoride-doped silicon carbide, calcium fluoride-doped silicon carbide, a heat dissipation component and an electronic device. Background Art

[0002] Silicon carbide (SiC) materials have broad development prospects in the high-tech field due to their excellent physical and chemical properties, such as high thermal conductivity, low expansion coefficient, high temperature resistance, high hardness, corrosion resistance, and oxidation resistance.

[0003] At present, the radiator mainly uses aluminum alloy materials, and the thermal conductivity of aluminum alloy materials is only 121-151 In order to further improve the thermal conductivity of the heat sink material, copper-aluminum composite, copper-silicon composite and aluminum-silicon composite materials are also used in small quantities in the heat sink material, which increases the thermal conductivity of the heat sink material to 200 , but this greatly increases the cost. In addition to the high cost, these composite materials also have disadvantages such as not resistant to high temperatures, easy to be corroded, and poor thermal stability.

[0004] Silicon carbide has high thermal conductivity, making it very suitable for use as a heat sink material. In addition, silicon carbide has very good stability under severe environmental disturbances (including drastic changes in temperature and humidity) or when exposed to corrosive and other chemically reactive environments, which can effectively avoid damage to heat sink components and improve heat sink performance. Therefore, silicon carbide is considered the best choice for heat sink materials.

[0005] However, the stable silicon-carbon bond makes it difficult to sinter silicon carbide, and the high sintering temperature and high mechanical strength make it difficult to process silicon carbide into complex structures, making the traditional silicon carbide preparation method complicated and costly, and the thermal conductivity of the prepared silicon carbide is poor. Summary of the invention

[0006] The present invention provides a method for preparing calcium fluoride-doped silicon carbide, calcium fluoride-doped silicon carbide, a heat dissipation component and an electronic device, so as to solve the defects of a traditional method for preparing silicon carbide in the prior art, namely, a complicated preparation process, a high preparation cost and poor thermal conductivity of the prepared silicon carbide, and realize the preparation of silicon carbide materials with better thermal conductivity at a lower cost and a higher efficiency.

[0007] The invention provides a method for preparing calcium fluoride-doped silicon carbide, comprising the following steps.

[0008] Using anhydrous ethanol as solvent and tetramethylammonium hydroxide as dispersant, calcium salt powder, acid solution and silicon carbide powder are mixed to obtain a suspension;

[0009] The obtained suspension is subjected to a hydrothermal reaction, and after the hydrothermal reaction is completed, the mixture obtained by the hydrothermal reaction is treated to obtain a composite powder;

[0010] The obtained composite powder is pressed into a green body, and then sintered to obtain calcium fluoride-doped silicon carbide.

[0011] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the reaction temperature of the hydrothermal reaction is 50-100° C., and the reaction time is 1-10 h.

[0012] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the mass of the tetramethylammonium hydroxide is 1-2% of the mass of the silicon carbide powder.

[0013] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the calcium salt powder includes any one of calcium carbonate powder, calcium hydroxide powder, calcium chloride powder and calcium sulfate powder.

[0014] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the acidic solution is a hydrogen fluoride solution.

[0015] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the calcium salt powder is calcium carbonate powder.

[0016] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the mass ratio of the calcium carbonate powder to the silicon carbide powder is 1:8-20.

[0017] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the solid content of the suspension is 40-60 vol%.

[0018] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, anhydrous ethanol is used as a solvent and tetramethylammonium hydroxide is used as a dispersant to mix calcium salt powder, an acidic solution and silicon carbide powder to obtain a suspension, comprising:

[0019] Dissolving calcium salt powder into hydrogen fluoride aqueous solution to form a homogeneous calcium salt powder-hydrogen fluoride solution;

[0020] Dispersing silicon carbide powder in anhydrous ethanol, adding the calcium salt powder-hydrogen fluoride solution to obtain a mixed solution;

[0021] Tetramethylammonium hydroxide is added to the mixed solution, and ultrasonic treatment is performed to obtain the suspension.

[0022] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the mixture obtained by the hydrothermal reaction is treated to obtain a composite powder, comprising:

[0023] The mixture obtained by the hydrothermal reaction is centrifuged and washed, and the precipitate is collected. The precipitate is dried, ground, granulated, sieved, and dried to obtain the composite powder.

[0024] According to a method for preparing calcium fluoride doped silicon carbide provided by the present invention, the sintering temperature is , the sintering time is 1-5h.

[0025] According to a method for preparing calcium fluoride-doped silicon carbide provided by the present invention, after the obtained composite powder is pressed into a green body, and sintered to obtain calcium fluoride-doped silicon carbide, the method further comprises:

[0026] Conduct density test, hardness test and thermal conductivity test on calcium fluoride doped silicon carbide;

[0027] In the case where the calcium fluoride doped silicon carbide passes the density test, the hardness test and the thermal conductivity test, it is determined that the calcium fluoride doped silicon carbide meets the qualified standard.

[0028] The present invention also provides a calcium fluoride-doped silicon carbide, comprising: prepared by any of the above-mentioned calcium fluoride-doped silicon carbide preparation methods.

[0029] The present invention also provides a heat sink element, comprising: the calcium fluoride-doped silicon carbide as described above.

[0030] The present invention also provides an electronic device, comprising: the radiator element as described above.

[0031] The invention provides a method for preparing calcium fluoride-doped silicon carbide, calcium fluoride-doped silicon carbide, a heat dissipation component and an electronic device. A uniformly doped calcium fluoride-silicon carbide composite powder is prepared by a hydrothermal reaction method, and the powder is granulated and dry-pressed to produce a green body. The green body is then sintered into a dense ceramic body. Since the melting point of calcium fluoride is much lower than that of silicon carbide, silicon carbide can be densified at a relatively low sintering temperature, thereby increasing the relative density and improving the hardness and thermal conductivity of the silicon carbide ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a schematic flow chart of the method for preparing calcium fluoride-doped silicon carbide provided by the present invention.

[0034] Figure 2 It is a schematic diagram of a density testing device used in the method for preparing calcium fluoride-doped silicon carbide provided by the present invention.

[0035] Figure 3 This is a scanning electron microscope photograph of the calcium fluoride-doped silicon carbide prepared in Example 1 and its energy dispersion X-ray spectrum.

[0036] Figure 4 1 is the XRD spectrum of calcium fluoride doped silicon carbide powder in different embodiments and comparative examples.

[0037] Figure 5 1 are scanning electron microscope photos of calcium fluoride-doped silicon carbide in different embodiments and comparative examples.

[0038] Figure 6 This is a graph showing the relationship between thermal conductivity, relative density, Vickers hardness and sintering temperature of calcium fluoride doped silicon carbide. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0041] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0042] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0043] Combine the following Figure 1-Figure 6 The invention describes a method for preparing calcium fluoride-doped silicon carbide.

[0044] Figure 1 Schematic diagram of the process of preparing calcium fluoride doped silicon carbide provided by the present invention, such as Figure 1 As shown, the method comprises the following steps: Step 101, using anhydrous ethanol as a solvent and tetramethylammonium hydroxide as a dispersant, mixing calcium salt powder, an acidic solution and silicon carbide powder to obtain a suspension;

[0045] Step 102, subjecting the obtained suspension to a hydrothermal reaction, and after the hydrothermal reaction is completed, treating the mixture obtained by the hydrothermal reaction to obtain a composite powder;

[0046] Step 103: Press the obtained composite powder into a green body, and sinter it to obtain calcium fluoride-doped silicon carbide.

[0047] Specifically, the embodiment of the present invention adds reactants: silicon carbide, acidic solution and calcium salt powder into a hydrothermal reactor for hydrothermal reaction, so that the calcium salt powder is evenly doped in the silicon carbide powder. Since the melting point of the calcium salt powder is much lower than the melting point of silicon carbide, the silicon carbide can be densified at a lower sintering temperature, thereby increasing the relative density and improving the hardness and thermal conductivity of the silicon carbide ceramic.

[0048] The embodiment of the present invention adopts a hydrothermal reaction to prepare calcium fluoride-doped silicon carbide, thereby improving the phenomenon of uneven doping caused by using a ball milling method to dope powder in the past.

[0049] As an optional embodiment, the calcium salt powder includes any one of calcium carbonate powder, calcium hydroxide powder, calcium chloride powder and calcium sulfate powder.

[0050] As an optional embodiment, the calcium salt powder is calcium carbonate powder.

[0051] Specifically, since calcium carbonate has low cost and high controllability of purity, the embodiment of the present invention selects calcium carbonate powder as calcium salt powder to prepare calcium fluoride doped silicon carbide. When silicon carbide, acidic solution and calcium carbonate undergo hydrothermal reaction, the reaction conditions are mild and the process is highly controllable, which can further reduce the preparation cost of preparing calcium fluoride doped silicon carbide and simplify the preparation process of preparing calcium fluoride doped silicon carbide.

[0052] As an optional embodiment, the calcium salt powder is a hydrogen fluoride solution.

[0053] Specifically, the embodiment of the present invention uses hydrogen fluoride solution as an acidic solution to prepare calcium fluoride-doped silicon carbide. When hydrogen fluoride reacts with calcium carbonate or other calcium-containing compounds, calcium fluoride can be directly and efficiently generated. This direct reactivity helps to simplify the preparation process, reduce intermediate steps, and improve production efficiency. By using a high-purity hydrogen fluoride solution and strictly controlling the reaction conditions, high-purity calcium fluoride can be prepared. This is crucial for subsequent doping in silicon carbide, because high-purity doping substances can ensure the excellent performance of the final product.

[0054] Moreover, the hydrothermal reaction of hydrogen fluoride solution, calcium carbonate and silicon carbide under appropriate conditions can achieve uniform doping of calcium fluoride in silicon carbide. This uniform doping helps to improve the overall performance of the composite material, such as hardness, wear resistance, thermal stability and chemical stability.

[0055] As an optional embodiment, the reaction temperature of the hydrothermal reaction is 50-100° C., and the reaction time is 1-10 h.

[0056] It should be noted that the reaction temperature of the hydrothermal reaction in the embodiment of the present invention needs to be controlled at 50-100° C. This reaction condition provides the energy required for the reaction of calcium carbonate and hydrogen fluoride solution, so that ΔG=ΔH-TΔS<0, and the reaction can proceed.

[0057] If the reaction temperature of the hydrothermal reaction is lower than 50°C, the hydrothermal reaction cannot proceed, and thus calcium fluoride cannot be generated; if the reaction temperature of the hydrothermal reaction is higher than 100°C, unnecessary energy waste is caused.

[0058] As an optional embodiment, the mass of tetramethylammonium hydroxide is 1-2% of the mass of the silicon carbide powder.

[0059] As an optional embodiment, the mass ratio of calcium carbonate powder to silicon carbide powder is 1:8-20.

[0060] Optionally, in some embodiments of the present invention, the mass ratio of calcium carbonate powder to silicon carbide powder is 1:8-20. Further, the molar ratio of calcium carbonate powder to hydrogen fluoride is 1:2. The above conditions define the ratio of calcium fluoride to silicon carbide.

[0061] Optionally, in some embodiments of the present invention, the mass of tetramethylammonium hydroxide is 1-2% of the mass of the silicon carbide powder.

[0062] In the present invention, the amount of calcium fluoride added and the amount of silicon carbide and tetramethylammonium hydroxide added need to be matched and added in a certain ratio, and a uniformly doped calcium fluoride-silicon carbide composite powder can be prepared by controlling the hydrothermal temperature and the raw material ratio and sintering without additional complicated steps.

[0063] As an optional embodiment, the solid content of the suspension is 40-60 vol%.

[0064] It should be noted that in the embodiment of the present invention, anhydrous ethanol is used as a solvent, tetramethylammonium hydroxide is used as a dispersant, and the solid content of the suspension obtained by mixing calcium salt powder, acidic solution and silicon carbide powder is 40-60vol%. If the solid content in the above suspension is too much, the total mass of the system will be increased, the interaction between particles will be enhanced, and agglomeration and sedimentation will be likely to occur, resulting in a decrease in the stability of the suspension. This instability may cause the suspension to stratify, precipitate and other phenomena during use, affecting the use effect. In addition, too high a solid content will cause the viscosity of the suspension to increase and the fluidity to deteriorate. In applications such as spraying and spraying, a suspension with poor fluidity is difficult to distribute evenly, which may cause problems such as uneven coating and uneven spraying of the liquid, affecting the use effect.

[0065] The solid particles in the suspension are the main carriers of the active ingredients. If the solid content in the suspension is too low, it means that the content of the active ingredients is also reduced accordingly, which may lead to a decrease in product performance and fail to meet usage requirements.

[0066] As an optional embodiment, anhydrous ethanol is used as a solvent and tetramethylammonium hydroxide is used as a dispersant to mix calcium salt powder, an acid solution and silicon carbide powder to obtain a suspension, including: dissolving calcium carbonate powder in a hydrogen fluoride aqueous solution to form a homogeneous calcium carbonate-hydrogen fluoride solution;

[0067] Dispersing silicon carbide powder in anhydrous ethanol, adding calcium carbonate-hydrogen fluoride solution to obtain a mixed solution;

[0068] Tetramethylammonium hydroxide was added to the mixed solution, and ultrasonic treatment was performed to obtain a suspension.

[0069] Specifically, ultrasound is conducive to the dissolution of tetramethylammonium hydroxide. In order to accelerate the dissolution, stirring is preferably performed during the ultrasound process. The ultrasound time is preferably 10-20 minutes, and the stirring time is preferably 20-30 minutes.

[0070] By preparing the suspension according to the above steps, a more uniformly dispersed suspension can be obtained, which provides conditions for the subsequent preparation of dense composite powders.

[0071] It should be noted that the ultrasonic frequency and the stirring speed are not specifically limited in the embodiments of the present invention.

[0072] By preparing the suspension according to the above steps, a more uniformly dispersed suspension can be obtained, which provides conditions for the subsequent preparation of dense composite powders.

[0073] As an optional embodiment, the mixture obtained by the hydrothermal reaction is processed to obtain a composite powder, including: centrifuging and washing the mixture obtained by the hydrothermal reaction, collecting the precipitate, drying the precipitate, grinding, granulating, sieving, and drying to obtain the composite powder.

[0074] It should be noted that the number of centrifugation and washing in the embodiment of the present invention is 2-3 times. The sieve used is a 100 mesh sieve.

[0075] As an optional embodiment, the sintering temperature is , the sintering time is 1-5h.

[0076] In the embodiment of the present invention, the dry-pressed silicon carbide green body is sintered into silicon carbide ceramics. If the sintering temperature is lower than 1450°C, the sintered SiC ceramics are not dense, which greatly affects the strength. Since the melting point of calcium fluoride is 1402°C, it will become a liquid phase above 1402°C. These liquid phases will accelerate the diffusion and mass transfer of silicon carbide during the sintering process, thereby promoting the densification process of silicon carbide sintering.

[0077] The calcium fluoride doped silicon carbide preparation method provided by the present invention only dopes a small amount of calcium fluoride, which will not affect the high thermal conductivity performance of silicon carbide. The addition of calcium fluoride greatly reduces the sintering temperature of silicon carbide while ensuring the thermal conductivity of silicon carbide, greatly reducing the production cost. The method is simple and efficient, and the operation is easy to control.

[0078] The method for preparing calcium fluoride-doped silicon carbide provided by the present invention specifically comprises the following steps:

[0079] Step 1: Calcium carbonate (CaCO 3 ) powder is added to the hydrogen fluoride (HF) aqueous solution and dissolved and stirred to form CaCO 3 -HF homogeneous solution.

[0080] Step 2: Weigh SiC powder according to the proportion and add it to CaCO 3 -HF homogeneous solution, and add an appropriate amount of anhydrous ethanol as a solvent to prepare a suspension with a solid content of 50 vol%.

[0081] Step 3, adding tetramethylammonium hydroxide (TMAH) as a dispersant to the suspension, mixing the suspension using ultrasound and a magnetic stirrer, pouring the suspension into a hydrothermal reactor, reacting at 50-100° C. for 1-10 hours to obtain a mixture, and cooling to room temperature.

[0082] Step 4: centrifuge and wash the reaction mixture to obtain a precipitate, then fully dry the precipitate, grind it with a mortar, granulate it, sieve it, and dry it to obtain a composite powder.

[0083] Step 5: Weigh an appropriate amount of powder and place it in a 9mm×9mm×1.5mm (length×width×height) mold and use a hydraulic press to unidirectionally press to obtain a green body.

[0084] Step 6: Place the green blank in step 5 Calcination , silicon carbide ceramics are obtained.

[0085] As an optional embodiment, after the obtained composite powder is pressed into a green body and sintered to obtain calcium fluoride-doped silicon carbide, the method further comprises: performing density testing, hardness testing and thermal conductivity testing on the calcium fluoride-doped silicon carbide;

[0086] Under the condition that the calcium fluoride doped silicon carbide passes the density test, the hardness test and the thermal conductivity test, it is determined that the calcium fluoride doped silicon carbide meets the qualified standard;

[0087] Conducting density testing on calcium fluoride doped silicon carbide, including: conducting density testing on calcium fluoride doped silicon carbide using the Archimedes drainage method to obtain the relative density of the calcium fluoride doped silicon carbide;

[0088] When the relative density of the calcium fluoride doped silicon carbide is not less than a preset value, determining that the calcium fluoride doped silicon carbide passes the density test;

[0089] The hardness test of calcium fluoride doped silicon carbide includes: embedding the calcium fluoride doped silicon carbide in a resin material by using an automatic hot embedding machine;

[0090] Using a grinding and polishing machine to grind and polish the mounted calcium fluoride doped silicon carbide to obtain calcium fluoride doped silicon carbide with surface polishing;

[0091] After the surface of the polished calcium fluoride-doped silicon carbide is pressurized and maintained for a preset time, a hardness value of the calcium fluoride-doped silicon carbide is read using a hardness tester;

[0092] The position of the calcium fluoride-doped silicon carbide is moved, and after repeated measurements are performed for multiple times, an average hardness value of the calcium fluoride-doped silicon carbide is obtained;

[0093] When the average hardness of the calcium fluoride doped silicon carbide is not less than the hardness threshold, determining that the calcium fluoride doped silicon carbide passes the hardness test;

[0094] Conducting a thermal conductivity test on calcium fluoride doped silicon carbide, including: using a laser thermal conductivity meter to test the calcium fluoride doped silicon carbide to obtain the thermal conductivity of the calcium fluoride doped silicon carbide;

[0095] When the thermal conductivity of the calcium fluoride doped silicon carbide is not less than the thermal conductivity threshold, it is determined that the calcium fluoride doped silicon carbide passes the thermal conductivity test.

[0096] The specific test steps for density testing of calcium fluoride doped silicon carbide using the Archimedes drainage method are as follows:

[0097] Mark the calcium fluoride-doped silicon carbide and place it in a beaker filled with distilled water. Boil the beaker in a spot heating mantle for 2 hours to fully expel the gas in the sintered body and allow water molecules to penetrate.

[0098] The boiled calcium fluoride doped silicon carbide was cooled in water, and the weight of calcium fluoride doped silicon carbide in water was measured using a density test device. and calcium fluoride doped silicon carbide wet weight .

[0099] Place the density test device on the balance and place a beaker filled with distilled water on the base. The distilled water in the beaker should completely immerse the colander. Place calcium fluoride-doped silicon carbide on the colander to weigh the weight of calcium fluoride-doped silicon carbide in water. , wipe the moisture on the surface of calcium fluoride doped silicon carbide with a wet filter paper, and place it on the top platform of the device to weigh the wet weight of calcium fluoride doped silicon carbide ;

[0100] in, Figure 2 Schematic diagram of the density testing device used in the method for preparing calcium fluoride-doped silicon carbide provided by the present invention. Figure 2 shown.

[0101] Place the boiled calcium fluoride-doped silicon carbide in a petri dish and dry it in a drying oven for 12 hours. After fully draining the water from the calcium fluoride-doped silicon carbide, weigh the dry weight of the dried calcium fluoride-doped silicon carbide with a balance. ;

[0102] Based on the three weights of calcium fluoride-doped silicon carbide measured experimentally, the actual density of calcium fluoride-doped silicon carbide can be calculated according to formula (1): .

[0103] (1)

[0104] in: Indicates the density of deionized water, 1g / cm 3 .

[0105] Theoretical density of calcium fluoride doped silicon carbide It can be calculated according to formula (2).

[0106] (2)

[0107] in: and They represent the mass fractions of calcium fluoride and silicon carbide respectively, in %. and They represent the theoretical density of calcium fluoride (3.18 g / cm 3 ) and the theoretical density of silicon carbide (3.21 g / cm 3 ).

[0108] Relative density of calcium fluoride doped silicon carbide , the actual density of calcium fluoride doped silicon carbide can be Theoretical density The ratio of can be calculated based on formula (3):

[0109] (3)

[0110] Obtaining the relative density of calcium fluoride doped silicon carbide Afterwards, the relative density of calcium fluoride-doped silicon carbide can be determined Is it not less than the preset value? In determining the relative density of calcium fluoride doped silicon carbide When the value is not less than the preset value, it can be determined that the calcium fluoride-doped silicon carbide passes the density test.

[0111] It should be noted that the preset value in the density test may be determined based on prior knowledge and / or actual conditions. The specific value of the preset value is not limited in the embodiment of the present invention.

[0112] The specific test steps for density testing of calcium fluoride doped silicon carbide are as follows:

[0113] The calcium fluoride doped silicon carbide obtained after sintering is embedded in the resin material by using an automatic hot embedding machine, and the embedded calcium fluoride doped silicon carbide is ground and polished by using a grinding and polishing machine to remove impurities on the test surface of the calcium fluoride doped silicon carbide and make the test surface smooth.

[0114] When the diamond indenter of the hardness tester is pressed on the test surface of calcium fluoride-doped silicon carbide with a force of 3 kg and the pressure is maintained for a certain period of time, a diamond indentation will appear on the test surface of calcium fluoride-doped silicon carbide.

[0115] The hardness value of calcium fluoride-doped silicon carbide can be read by drawing the four vertices of the indentation using the test software equipped with the hardness tester.

[0116] By moving the position of the calcium fluoride-doped silicon carbide and repeating the measurement for multiple times, multiple hardness values ​​of the calcium fluoride-doped silicon carbide can be obtained.

[0117] The hardness values ​​of a plurality of calcium fluoride-doped silicon carbides are averaged to obtain an average hardness value of the calcium fluoride-doped silicon carbide.

[0118] After obtaining the average hardness value of the calcium fluoride doped silicon carbide, it can be determined whether the average hardness value of the calcium fluoride doped silicon carbide is not less than the hardness threshold. If it is determined that the average hardness value of the calcium fluoride doped silicon carbide is not less than the hardness threshold, it can be determined that the calcium fluoride doped silicon carbide passes the hardness test.

[0119] It should be noted that the hardness threshold in the hardness test may be determined based on prior knowledge and / or actual conditions. The specific value of the hardness threshold is not limited in the embodiment of the present invention.

[0120] The specific test steps for thermal conductivity testing of calcium fluoride doped silicon carbide are as follows:

[0121] The thermal conductivity of calcium fluoride doped silicon carbide was tested using a laser thermal conductivity meter. The test sample size was 9 mm × 9 mm × 1.5 mm (length × width × height). The test was carried out at room temperature while maintaining a nitrogen atmosphere.

[0122] Since there is a measurement deviation of 5%-8% when testing with a laser thermal conductivity meter, in the embodiment of the present invention, the laser thermal conductivity meter is used to measure the calcium fluoride doped silicon carbide multiple times and then the average value is taken as the thermal conductivity of the calcium fluoride doped silicon carbide.

[0123] Thermal conductivity It can be calculated according to formula (4):

[0124] (4)

[0125] in, Indicates volume density in g·cm -3 ; Represents the thermal diffusion coefficient in units of ; Indicates the specific heat capacity of the material, in units of ; Represents thermal conductivity in units of .

[0126] After obtaining the thermal conductivity of the calcium fluoride doped silicon carbide, it can be determined whether the thermal conductivity of the calcium fluoride doped silicon carbide is not less than the thermal conductivity threshold. When it is determined that the thermal conductivity of the calcium fluoride doped silicon carbide is not less than the thermal conductivity threshold, it can be determined that the calcium fluoride doped silicon carbide passes the thermal conductivity test.

[0127] In order to facilitate the understanding of the method for preparing calcium fluoride-doped silicon carbide provided by the present invention, the method for preparing calcium fluoride-doped silicon carbide provided by the present invention is described below through some specific examples and comparative examples.

[0128] Example 1

[0129] This embodiment provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0130] Step 1: weigh 1.5 g of CaCO 3 The powder was added into 3 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0131] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0132] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0133] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0134] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0135] Step six, calcining the green body in step five at 1450° C. for 2 hours to obtain silicon carbide ceramics.

[0136] Example 2

[0137] This embodiment provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0138] Step 1: weigh 2.2 g of CaCO 3 The powder was added into 5 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0139] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0140] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0141] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0142] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0143] Step six, calcining the green body in step five at 1450° C. for 2 hours to obtain silicon carbide ceramics.

[0144] It should be noted that in step 1 of Example 2, CaCO 3 The dosage of the powder is 2.2 g, the dosage of the HF solution is 5 ml, and the rest is the same as in Example 1.

[0145] Example 3

[0146] This embodiment provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0147] Step 1: weigh 3.7 g of CaCO 3 The powder was added into 10 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0148] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0149] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0150] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0151] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0152] Step six, calcining the green body in step five at 1450° C. for 2 hours to obtain silicon carbide ceramics.

[0153] It should be noted that in step 1 of Example 3, CaCO 3 The dosage of the powder is 3.7 g, the dosage of the HF solution is 10 ml, and the rest is the same as in Example 1.

[0154] Example 4

[0155] This embodiment provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0156] Step 1: weigh 1.5 g of CaCO 3 The powder was added into 3 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0157] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0158] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0159] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0160] Step 5: Add CaF 2-SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0161] Step six, calcining the green body in step five at 1500° C. for 2 hours to obtain silicon carbide ceramics.

[0162] It should be noted that the sintering temperature in step 6 of Example 4 is 1500° C., and the rest is the same as Example 1.

[0163] Example 5

[0164] This embodiment provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0165] Step 1: weigh 1.5 g of CaCO 3 The powder was added into 3 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0166] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0167] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0168] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0169] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0170] Step six, calcining the green body in step five at 1600° C. for 2 hours to obtain silicon carbide ceramics.

[0171] It should be noted that the sintering temperature in step 6 of Example 5 is 1600° C., and the rest is the same as Example 1.

[0172] Comparative Example 1

[0173] This comparative example provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0174] Step 1: weigh 1.5 g of CaCO 3 The powder was added into 3 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0175] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0176] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 40 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0177] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0178] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0179] Step six, calcining the green body in step five at 1450° C. for 2 hours to obtain silicon carbide ceramics.

[0180] It should be noted that the hydrothermal reaction temperature in step 3 of comparative example 1 is 40° C., and the rest is the same as in example 1. Results No calcium fluoride-silicon carbide composite powder can be obtained after post-reaction treatment.

[0181] Comparative Example 2

[0182] This comparative example provides a method for preparing calcium fluoride-doped silicon carbide, the steps are as follows:

[0183] Step 1: weigh 1.5 g of CaCO 3 The powder was added into 3 ml of HF solution, dissolved by ultrasonication for 20 min, and stirred for 30 min to form a Ca-F homogeneous solution.

[0184] Step 2: weigh 30 g of SiC powder, measure 70 ml of anhydrous ethanol, add the powder to the anhydrous ethanol, and then add it to the Ca-F homogeneous solution prepared in step 1 to prepare a suspension with a solid content of 50 vol%.

[0185] Step 3: Add 0.46 g of TMAH as a dispersant to the prepared suspension, dissolve it by ultrasonication for 20 min, stir it magnetically for 30 min to form a homogeneous suspension, pour the suspension into a 100 ml hydrothermal reactor, react at 60 ° C for 2 h, obtain a mixture, and cool it to room temperature.

[0186] Step 4: The mixture was placed into two 50 ml centrifuge tubes, and centrifuged and washed 2-3 times to obtain a precipitate. The obtained powder was then dried in a vacuum drying oven at 90°C for 24 hours to obtain CaF 2 -SiC composite powder.

[0187] Step 5: Add CaF 2 -SiC composite powder was ground in a mortar, granulated, sieved, and then dried in a vacuum drying oven at 90°C for 24 hours. The composite powder was weighed and placed in a 9mm×9mm×1.5mm (length×width×height) mold and unidirectionally pressed by a hydraulic press to obtain a green body.

[0188] Step six, calcining the green body in step five at 1300° C. for 2 hours to obtain silicon carbide ceramics.

[0189] It should be noted that the sintering temperature in step 6 of comparative example 2 is 1300° C., and the rest is the same as in example 1. Results After the reaction, dense calcium fluoride-doped silicon carbide cannot be obtained.

[0190] Figure 3 The following is a scanning electron microscope photograph of calcium fluoride doped silicon carbide prepared in Example 1 and its energy dispersion X-ray spectrum. Figure 3 It can be seen that the calcium fluoride-doped silicon carbide powder prepared by the calcium fluoride-doped silicon carbide preparation method provided by the present invention does not produce agglomeration phenomenon. Energy dispersive X-ray spectroscopy (EDS) analysis shows that calcium and fluorine elements are evenly distributed, which can prove that the calcium fluoride-doped silicon carbide is evenly doped.

[0191] Figure 4 1 is the XRD spectrum of calcium fluoride doped silicon carbide powder in different embodiments and comparative examples. Figure 4As shown, in Comparative Example 1, the hydrothermal temperature is 40°C and calcium fluoride cannot be generated, and the spectrum is pure silicon carbide. However, in Example 3, the hydrothermal temperature is 60°C, and the reaction successfully generates calcium fluoride, and the peak of calcium fluoride is clear, indicating that the crystallinity of calcium fluoride is good.

[0192] Figure 5 2 are scanning electron microscope photos of calcium fluoride doped silicon carbide in different embodiments and comparative examples. Figure 5 As shown, at 1450-1600°C (Example 1, Example 4, Example 5), the calcium fluoride doped silicon carbide obtained after sintering has good density and no obvious pores, while the calcium fluoride doped silicon carbide obtained by sintering at 1300°C (Comparative Example 2) has obvious pores.

[0193] Figure 6 This is a graph showing the relationship between the thermal conductivity, relative density, Vickers hardness and sintering temperature of calcium fluoride doped silicon carbide. Figure 6 As shown in the figure, at sintering temperatures of 1450℃, 1500℃, 1550℃ and 1600℃, the relative density of calcium fluoride doped silicon carbide is 94.8%, 95.3%, 97.1% and 90% respectively. The relative density shows a trend of first slightly increasing and then decreasing with the increase of sintering temperature. This is because the melting point of calcium fluoride is 1402℃, and it will become a liquid phase above 1402℃. These liquid phases will accelerate the diffusion and mass transfer of silicon carbide during the sintering process, improve the sintering activity of silicon carbide grains, reduce the sintering temperature, and help accelerate the densification process.

[0194] However, if the sintering temperature is too high, part of the molten calcium fluoride will penetrate downwards between the gaps in the green body, and part will evaporate upwards, leaving pores in the sintered body, which has a decisive influence on the relative density of the sintered body. The optimal sintering temperature is around 1550°C.

[0195] Generally speaking, a ceramic body having a relative density higher than 95% is regarded as a dense ceramic body. The calcium fluoride-doped silicon carbide sintered at sintering temperatures of 1500° C. and 1550° C. in the present invention is a dense silicon carbide ceramic body.

[0196] At sintering temperatures of 1450℃, 1500℃, 1550℃, and 1600℃, the Vickers hardness of calcium fluoride doped silicon carbide is 2753Hv, 2826Hv, 2966Hv, and 2563Hv, respectively. The Vickers hardness also shows a trend of first slightly increasing and then decreasing with the increase of sintering temperature. Since the relative density and grain size of the material are the key factors affecting the hardness of the material, the higher the density and the finer the grains, the higher the hardness. Figure 4The microscopic photograph of calcium fluoride doped silicon carbide in FIG. 1 can prove that the maximum hardness is obtained at 1550° C. The Vickers hardness of pure silicon carbide is usually between 2800 and 3400 HV. The calcium fluoride doped silicon carbide prepared by the present invention does not affect the Vickers hardness of silicon carbide.

[0197] At sintering temperatures of 1450°C, 1500°C, 1550°C, and 1600°C, the thermal conductivity of calcium fluoride-doped silicon carbide is 238 , 223 , 260 , 251 As the sintering temperature increases, the thermal conductivity of the material shows an irregular change pattern, and there is no continuous increase or decrease in thermal conductivity caused by the increase in sintering temperature. According to the above experimental results, the calcium fluoride doped silicon carbide obtained in Example 4 achieves the highest density, the highest hardness and the highest thermal conductivity.

[0198] The present invention also provides calcium fluoride-doped silicon carbide, which is prepared by the above preparation method.

[0199] The present invention also provides a heat sink component, comprising the calcium fluoride-doped silicon carbide.

[0200] The present invention also provides an electronic device, comprising a radiator element.

[0201] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing calcium fluoride-doped silicon carbide, characterized in that: include: Using anhydrous ethanol as solvent and tetramethylammonium hydroxide as dispersant, calcium salt powder, acid solution and silicon carbide powder are mixed to obtain a suspension; The obtained suspension is subjected to a hydrothermal reaction, and after the hydrothermal reaction is completed, the mixture obtained by the hydrothermal reaction is treated to obtain a composite powder; The obtained composite powder is pressed into a green body, and then sintered to obtain calcium fluoride-doped silicon carbide; The reaction temperature of the hydrothermal reaction is 50-100°C and the reaction time is 1-10h; The acidic solution is a hydrogen fluoride solution; The calcium salt powder is calcium carbonate powder; The mass ratio of the calcium carbonate powder to the silicon carbide powder is 1:8-20; The sintering temperature is 1150° C. and the sintering time is 1-5 hours.

2. The method for preparing calcium fluoride-doped silicon carbide according to claim 1, characterized in that: The mass of the tetramethylammonium hydroxide is 1-2% of the mass of the silicon carbide powder.

3. The method for preparing calcium fluoride-doped silicon carbide according to claim 1, characterized in that: The solid content of the suspension is 40-60 vol%.

4. The method for preparing calcium fluoride-doped silicon carbide according to claim 1, characterized in that: The method uses anhydrous ethanol as a solvent and tetramethylammonium hydroxide as a dispersant to mix calcium salt powder, an acid solution and silicon carbide powder to obtain a suspension, comprising: Dissolving calcium salt powder into hydrogen fluoride aqueous solution to form a homogeneous calcium salt powder-hydrogen fluoride solution; Dispersing silicon carbide powder in anhydrous ethanol, adding the calcium salt powder-hydrogen fluoride solution to obtain a mixed solution; Tetramethylammonium hydroxide is added to the mixed solution, and ultrasonic treatment is performed to obtain the suspension.

5. The method for preparing calcium fluoride-doped silicon carbide according to claim 1, characterized in that: The step of treating the mixture obtained by the hydrothermal reaction to obtain a composite powder comprises: The mixture obtained by the hydrothermal reaction is centrifuged and washed, and the precipitate is collected. The precipitate is dried, ground, granulated, sieved, and dried to obtain the composite powder.

6. The method for preparing calcium fluoride-doped silicon carbide according to any one of claims 1 to 5, characterized in that: After the obtained composite powder is pressed into a green body and sintered to obtain calcium fluoride-doped silicon carbide, the method further comprises: Conduct density test, hardness test and thermal conductivity test on calcium fluoride doped silicon carbide; In the case where the calcium fluoride doped silicon carbide passes the density test, the hardness test and the thermal conductivity test, it is determined that the calcium fluoride doped silicon carbide meets the qualified standard.

7. A calcium fluoride doped silicon carbide, characterized in that: include: The silicon carbide doped with calcium fluoride is prepared by the preparation method of calcium fluoride doped with silicon carbide according to any one of claims 1 to 6.

8. A radiator element, characterized in that: include: Calcium fluoride doped silicon carbide as claimed in claim 7.

9. An electronic device, characterized in that: include: The heat sink element of claim 8.

Citation Information

Patent Citations

  • Preparation method of modified micro-granules

    CN103418316A

  • Negative electrode material and preparation method thereof, battery and terminal

    CN112838197A